2019
DOI: 10.1111/cpr.12577
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of N‐myc expression sensitizes human neuroblastoma IMR‐32 cells expressing caspase‐8 to TRAIL

Abstract: Objectives: This study aims to explore the roles of N-myc and caspase-8 in TRAIL-resistant IMR-32 cells which exhibit MYCN oncogene amplification and lack caspase-8 expression. Materials and methods:We established N-myc-downregulated IMR-32 cells using shRNA lentiviral particles targeting N-myc and examined the effect the N-myc inhibition on TRAIL susceptibility in human neuroblastoma IMR-32 cells expressing caspase-8. Results:Cisplatin treatment in IMR-32 cells increased the expression of death receptor 5 (DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…NMYC amplification in NB has been implicated in resistance to apoptotic pathways ( 56 , 57 ) including resistant to TRAIL-induced apoptosis ( 58 ) where previous studies have demonstrated the synergistic proapoptotic effect of combined TRAIL treatment in MYCN-negative neuroblastoma cells expressing caspase-8 following IFN-γ treatment ( 58 ). In our model, ONC201 and ONC206 effectively induced apoptosis in both cell lines, with ONC206 exhibiting a more potent effect with a dose 10× lower than that of ONC201.…”
Section: Discussionmentioning
confidence: 99%
“…NMYC amplification in NB has been implicated in resistance to apoptotic pathways ( 56 , 57 ) including resistant to TRAIL-induced apoptosis ( 58 ) where previous studies have demonstrated the synergistic proapoptotic effect of combined TRAIL treatment in MYCN-negative neuroblastoma cells expressing caspase-8 following IFN-γ treatment ( 58 ). In our model, ONC201 and ONC206 effectively induced apoptosis in both cell lines, with ONC206 exhibiting a more potent effect with a dose 10× lower than that of ONC201.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in these cells, the downregulation of MYCN expression and restoration of caspase-8 expression induced apoptosis by activating TRAIL pathway. Pretreatment the cells with cisplatin dramatically enhanced TRAIL cytotoxicity via DR5 expression increased (Lee et al, 2019). In our study, combination of rapamycin and MK-2206 produced a synergistic effect in MYCN-amplified cell lines (NGP and BE2), but this synergistic effect was not observed in cell lines without MYCN amplification (AS and SY5Y).…”
Section: Discussionmentioning
confidence: 44%